Factorial Structure, Validity and Reability of the Nomophobia Scale in Students at a State University of Lima Metropolitana - Franco-Guanilo, Roxana (2022)
Nomophobia understood as fear of not being able to contact or make use of a smartphone, irrational fear of losing it, running out of batteries or being without an internet signal, which generates high rates of anxiety.  The consumer behaviors of this virtual society lead to the postponement of personal, academic and work objectives because more time is spent performing online activities, which turn out to be more attractive and less complex.   The main objective of this research has been to determine the factorial structure, validity and reliability of the Nomophobia Scale (NMPQ).  300 students participated in a State University of Metropolitan Lima. The confirmatory factor analysis corroborated a structure of four factors, showing adequate adjustment indicators composed of CFI= .997, TLI= 0.997 and RMSEA= 0.084. confirming a second-order model, plus a first-order model. Cronbach's alpha coefficient was .964, reliability for each factor greater than .70 indicating high composite reliability (CF) and extracted mean variance (AVE) with scores greater than .50 indicating adequate convergence in all factors.  It is concluded that the NMPQ is a valid and reliable instrument to measure nomophobia.